(untitled) (Fiep Bulletin - online, 2013)
Parkinson’s disease (DP) patients are attacked by many symptoms, mainly motors, that develops as time goes by, and, the disturbance on the gait gain a place of high light because progressively affects the mobility and independency of the PD patients. Many studies have been done using visual and auditory cues during the training of the gait, aiming to correct the alterations caused by PD, and in general it showing positives results, however, the studies analyzing the effects of the auditory and visual cues simultaneous are rare. In light of the need for further research established above, this study has as aim analyse the effects of auditory and visual cues on the gait patterns of PD patient. The subject recruited for this research descriptive of the type case study was a 76-year-old woman who had been diagnosed with PD 2 years ago. The subject completed walking trial in four different conditions: analyses of the gait with free speed without external cues (WC); analyses of the gait with audio cues (AC); analyse of the gait with visual cues (VC); analyses of the gait with audio and visual cues simultaneous (AVC). For the comparison among the different analyzed situations an ANOVA was applied (p? 0,05). Significant differences were verified (p<0,01) if compared WC with situation VC and AVC for the variable TLC, LRS and LLS. Besides, for the variable speed, only the situation VC was significantly different (p<0,05) of WC. In general, could be claimed that the visual cues approximated the pattern of the gait of the analyzed individual’s of the normal pattern of the gait for healthy elderly. High light the fact that because of the interventions have been made only once, the individual could have had difficulties in synchronize the gait with both types of cues because of ability lack, specially in situation with the two types of cues simultaneous, possibly causing influence on the results in this study.